Effectiveness of talent management strategies in developing employee potential and reducing turnover intention - Pa'wan, Fatimah; Juhdi, , Nurita; Hamsaram, Rammiklah@Simranpreet Kaur; Kassim, Norizan (2012)
The objectives of the study were to examine the effectiveness of talent management strategies used in organizations on developing employee potential and reducing turnover intention. Three hundred and thirty two employees participated in the study. Five dimensions of talent management were studied - open climate, communication, managing performance, employee development and rewards. Employee potential was measured using three dimensions – high performance, people agility and growth potential. These dimensions were identified using factor analysis on the items used to measure employee potential. The Pearson’s correlation tests indicated communication was significantly related to turnover intention with negative direction. The other four talent management dimensions were not significantly related to turnover intention. All the three employee potential dimensions were significantly related to talent management dimensions with positive direction. As for employee potential dimensions and turnover intention, only people agility was found significantly related to turnover. The other two dimensions – high performance and growth potential - were not significantly related. Further test using multiple linear regressions indicated that both high performance and people agility were significantly predicted by employee development, open climate and communication.